Home electrical appliances smart system - Husin, Siti Huzaimah; Ngahdiman, A A; Hashim, Nik Mohd Zarifie; Yusop, Yusmarnita; Ja'afar, Abd Shukur (IJCSMC, 2013)
A Smart Home is designed for the future home system that will be equipped with latest technology and given leisure for people. Hence the Smart Home will give a big impact in home design and will be the main target in a research and development (R&D) and business in the future. In this project Programmable Logic Controller (PLC) will be rolled as the primary control unit of the whole system. The main idea is about the new generation of homes. Smart homes are actually ordinary homes turned extraordinary using the latest technology. A smart home is nearly fully automated and it ensures safety, security and comfort for everyone under its roof. By utilizing advance and complex technologies, life is made easier and simpler. As a conclusion, this project was actually significantly can prevent problems that happened to present home automation system. This system will enable user to control their home appliances by using SMS. A web cam or CCTV for the capturing real time video are recommended to be in the future work as the user can also see the video from the distance. Keywords— Global System for